Utilizing mineral sequestration technology for enhanced performance of concrete containing basic oxygen furnace slag - Omarova Zhaniya; Ualiyev Dulat; Shon Chang-Seon; Zhang Dichuan; Kim Jong Ryeol (E3S Web of Conferences)
Basic oxygen furnace slag (BOFS) is a widely available by product of the steel-making industry that poses high interest for scientists in various fields. The carbon capture potential of BOFS is proven to be high. However, its further uses are actively investigated. BOFS is particularly attractive as a construction material due to its hydraulic reactivity and good strength, making it suitable for use as binding material and aggregate in concrete. However, it has a major drawback - unstable compounds that lead to material deterioration caused by volumetric expansion. Most of the research in the field focuses on the processing of BOFS in laboratory or industrial settings to eliminate the expensive products inside the slag and make it more durable. The suitability of using mineral sequestration technology instead of artificially accelerated carbonation has not yet been studied well. This research aimed to identify the main properties of the mortar mixes containing BOFS that underwent mineral sequestration over a long period to assess the technology’s feasibility. The correlation with quantitative data from thermogravimetric analysis (TGA) was also identified. Based on test results, the correlation between aging conditions and CO2 uptake was established, indicating that stockpiled and wet/dry cycle conditions were the most optimal aging methods for BOFS to achieve the highest carbonation (4.15-5.15%), hence the maximum stabilization degree of aggregates.